Rapid Prototyping of Topology Control Algorithms by Graph Transformation - Kulcsár, Géza; Stein, Michael; Schweizer, Immanuel; Varró, Gergely; Mühlhäuser, Max; Schürr, Andy (Electronic Communications of the EASST, 2014)
Topology control algorithms are used to improve the energy efficiency (or other quality parameters) of wireless sensor networks. In this paper, we propose a model-driven rapid prototyping approach for the kTC topology control algorithm to enable the fast implementation and the evaluation of its different variants, and consequently, to accelerate the network quality experimentation cycle. In our approach, wireless sensor networks are described by graph-based models, and three variants of the kTC topology control algorithm are implemented by graph transformation, which are then executed on input network descriptions to derive modified topologies whose quality is then measured in several contexts to be able to assess the achieved network quality improvement.